Genotoxicity in primary human peripheral lymphocytes after exposure to radiopacifiers in vitro - Braz, Mariana Gobbo [UNESP]; Marcondes, Joao Paulo de Castro [UNESP]; Matsumoto, Mariza Akemi; Duarte, Marco Antonio Hungaro; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Daniel Araki (Springer, 2008)
Taking into consideration that DNA damage plays an important role in carcinogenesis, the purpose of this study was to evaluate whether some radiopacifiers widely used in clinical practice are able to induce genetic damage in primary human cells in vitro. Human peripheral lymphocytes obtained from 10 healthy volunteers were exposed to barium sulphate (BaSO(4)), zirconium oxide (ZnO(2)) and bismuth oxide (Bi(2)O(3)) at final concentrations ranging from 1 to 1000 mu g/mL for 1 h at 37 degrees C. The negative control group was treated with vehicle control (phosphate buffer solution) for 1 h at 37 degrees C and the positive control group was treated with hydrogen peroxide (at 100 mu M) for 5 min on ice. Results were analyzed by the Friedman non-parametric test. The results pointed all compounds tested out did not induce DNA breakage in human peripheral lymphocytes as depicted by the mean tail moment and tail intensity in all concentrations tested. In summary, our results indicate that exposure to these radiopacifiers may not be a factor that increases the level of DNA lesions in human peripheral lymphocytes as detected by single cell gel (comet) assay.